Extensive subcutaneous fat necrosis complicated by neonatal hypercalcaemia - Al-Ghamdi, Waad M; Milyani, Asmaa Adel; Al-Agha, Abdulmoein Eid (Acta Biomedica Atenei Parmensis, 2021)
subcutaneous fat necrosis is a benign and often self-limiting inflammatory disorder experienced by newborns who were exposed to perinatal stress in the form of asphyxia, hypothermia, cord prolapse, and/or sepsis. lesions are usually benign and self-limiting, with complete resolution anticipated within a few weeks up to 6 months. they can be accompanied by multiple complications. of which the most significant and of life-threatening potential is neonatal hypocalcaemia. if not timely anticipated and adequately treated, the patient might deteriorate due to dehydration and acute renal failure. symptoms of neonatal hypercalcaemia can be variable in this age group, transcending from a nonspecific presentation of irritability, poor feeding, vomiting and constipation to the well-recognised polyuria, polydipsia, and dehydration. therapeutic options are provided through initial hyperrehydration and calcium wasting diuretics, switching feeds to a low calcium and vitamin D formula milk, institution of systemic steriods and if necessary, inititating bisphosphonate therapy in hypercalcaemia that is severe, recalcitrant to the previously mentioned treatment modalities, and/or when a rapid decrease in serum calcium levels is desired. in this report we describe a case of a 10 month old female infant with moderate neonatal hypercalcaemia as a complication of extensive SCFN manifestating by the age of 10 days and persisting into a prolonged clinical course of up to 9 months until most of the lesions were resolved.